Major causes of insuline resistance - Ewa Lidia Krzewicka-Romaniuk; Dagna Agnieszka Siedlecka; Anna Pradiuch; Grażyna Wójcicka (Kazimierz Wielki University, 2019)
Causes of insulin resistance can be divided into innate and secondary. There are many reasons for insulin resistance, including genetic mutations like insulin receptor mutations, hormonal and pharmacological or immunological. However insulin resistance is most commonly associated with obesity. Obesity is associated with a low-grade inflammation of white adipose tissue (WAT) resulting from chronic activation of the innate immune system and which can subsequently lead to insulin resistance, impaired glucose tolerance and diabetes.